2021
DOI: 10.1111/iju.14645
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and reproductive technology use in testicular cancer survivors in Japan: A multi‐institutional, cross‐sectional study

Abstract: To evaluate fertility and use of reproductive technology of testicular cancer survivors in a multi-institutional, cross-sectional study. Methods: This study recruited testicular cancer survivors who were followed after treatment for testicular cancer at eight high-volume institutions between 2018 and 2019. The participants completed the questionnaires on marital status, fertility and use of reproductive technology. Results: A total of 567 testicular cancer survivors, with a median age of 43 years, responded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…3 TC survivors frequently experience psychological burdens, physical and sexual dysfunction, infertility, loss of income, and fear of recurrence. 4,5 Financial toxicity (FT) is an economic side effect of cancer treatment, which arises from the subjective financial distress (FD) and objective financial burden (FB) of patients who undergo cancer treatments. 6 Cancer patients are anxious and uncomfortable with their condition and are mentally burdened by increased spending and reduced wealth stemming from cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 TC survivors frequently experience psychological burdens, physical and sexual dysfunction, infertility, loss of income, and fear of recurrence. 4,5 Financial toxicity (FT) is an economic side effect of cancer treatment, which arises from the subjective financial distress (FD) and objective financial burden (FB) of patients who undergo cancer treatments. 6 Cancer patients are anxious and uncomfortable with their condition and are mentally burdened by increased spending and reduced wealth stemming from cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, standard chemotherapies for TC such as bleomycin, etoposide, and cisplatin may cause long‐term adverse events 3 . TC survivors frequently experience psychological burdens, physical and sexual dysfunction, infertility, loss of income, and fear of recurrence 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 57.8% of male patients failed to discuss fertility preservation with the doctors prior to tumor treatment [ 9 ]. However, 87% of testicular tumor survivors were willing to preserve their spermatozoa by freezing [ 13 ]. Although the COVID-19 pandemic had a significant impact on the medical environment, the numbers of patients undergoing autologous sperm cryopreservation in our bank was still close to the numbers recorded for 2017–2019, moreover, 74.3% and 57.5% of annual cases was cancer patients in 2020 and 2021.…”
Section: Discussionmentioning
confidence: 99%
“…A study on post-cisplatin-treated fertility in testicular germ cell cancer survivors demonstrated a higher sperm preservation rate and higher paternity rate compared to those not using cryopreserved sperms, treated with 4 cycles of cisplatin therapy [112]. The researchers suggested the clinicians should consider not only the prevention of recurrence, but also the post-treatment fertility status, particularly in younger male patients [112]. Contrarily, a rat study of chemically induced TC reported a decrease in fertility following cisplatin treatment, which was recovered by the anticancer drug, quercetin [113].…”
Section: Testicular Cancermentioning
confidence: 99%